Behaviour of industrial prices in India - "Chatterji, Ruchira" (Delhi, 1989)
The behaviour of industrial prices and especially the flexibility of industrial prices in relation to demand have been central issues in economics with wide-ranging implications at both the micro and macro levels. Whether variations in demand are met by price or quantity adjustments is a question which lies at the heart of micro economic theories of the firm and industrial pricing, while at the macroeconomic level the behaviour of industrial prices has important consequences for inflation, in particular whether the indusrial price is only a transmission belt in the inflationary process or an independent source of inflation.
Keywords: Industrial productivity India